Does Social Capital impact Human Capital: The Case of Scheduled Tribes of Keralam - Balakrishnan. U; Hari Kurup. K. K; N.Karunakaran (Journal of Advanced Research in Operational and Marketing Management, 2026)
The study aims to investigate and establish the efficacy of social capital in enhancing the human capital of the scheduled tribes in Keralam. Social capital, characterised by social network relationships, plays a pivotal role in fostering people’s development by facilitating economic growth through cooperation and coordination. It encompasses three dimensions: bonding, bridging, and linking. Primary data were collected from the major tribes in the Kasaragod district of Keralam, namely Mavilan, Marati, and Malavettuvan. The social capital endowment of the scheduled tribes was evaluated based on a social capital index that combines various dimensions of social capital. The study utilised descriptive statistical analyses to determine the significance of social capital in relation to the respondents’ years of schooling and body mass index (BMI). The findings indicate a significant relationship between the average years of schooling among scheduled tribes and their social capital. However, it is noteworthy that there is only a slight difference in the BMI of the scheduled tribes. It is suggested that social capital exerts a more pronounced influence on the education of the scheduled tribes rather than their health.